Dramatización como recurso para fomentar el hábito de lectura en los estudiantes de primaria - Fernández Rodríguez, Juan Carlos (2022)
Promoting a reading habit is essential for a student and a society. It means that humanity knowledge will not be lost and on the contrary, it will be improved with new contributions to face future adversities. Thus, this paper entitled: Dramatization as a resource to promote the reading habit in elementary students has the purpose of implementing this resource to promote the reading habit. The dramatization as a resource is supposed to be a support to the teacher work through the staging of the previous read facts; while the reading habit is a recurring act aimed at decoding texts. Applying this resource fulfilled the proposed purpose evidenced in the initial problems improvement of the of the students, e.g.: spelling errors, the deficit in the inferential and critical levels and writing incoherence. Besides, there were benefits beyond what was planned.